Classification of voltage sags according to the severity of the effects on the induction motor (2015)
In this paper, symmetrical and unsymmetrical voltage sags are classified according to the severity of the effects produced on the behavior of induction motors, using the double-cage rotor model. The analyzed variables are: current and torque peaks, and speed loss in transient and steady states. The severity of these effects is analyzed with 14640 voltage sags, both at the beginning of the voltage sag and when the voltage is recovered, by changing the type, magnitude, duration, and initial-point-of-wave. Four mechanical torque loads were used for the analysis, three with constant behavior and one with quadratic behavior. The results show the durations and initial-point-of-wave with more severe effects for each type of voltage sag. Finally, a classification that depends on the type of voltage sag and the variable of interest is obtained.